Experimental study of paver blocks using palm shell and coconut shell. (2022) - Indhiradevi, P.; Selvamuhil, A.K.; Vengainayaki, V.; Gokul, G.
Abstract: Now a days construction industry is one of the leading and developing industries. Due to increase in population, the industrialization and need for the construction is also increased. In present scenario people are in search of alternative material for the construction of building as a result of increase in cost of construction materials. Paver blocks are mostly used in places of driveway, pavement, footpath, walkway in cities etc. This study aims to make the paver blocks by using Palm and coconut shell. Palm and coconut shell are easily available materials in all the regions, especially in tropical areas. Hence, the paver blocks replacing the coarse aggregates at a rate of 20% and 40% by Palm and coconut shells are casted. It is one of the cost efficient products used by low level people also. The process of using the Palm and coconut shell is considered as one of the waste management system. The agricultural wastes are reused in various ways. It is considered as an effective method of reusing palm and coconut shell by making a slight decrease in the cost of construction material. This result shows the utilization of natural material and these paver blocks are used on various areas like gardens, low traffic areas, and where the minimum load applied, based on their compressive strength their usage may differ. However, this study also found that, this type of manufacturing paver blocks give benefit to both the producer and the customer economically.